A Footnote to Dolf Seilacher's Study on Neonereites biserialis Based on New Evidence from the Upper Cretaceous of Antarctica. Issue 1 (2nd January 2016) - Olivero, Eduardo B.; López Cabrera, María Isabel
Abstract: The irregular meandering, endichnial trace fossil Nereites biserialis characterized by alternating biserial row of dimples flanked by even to lobate laminae of sediment, best observed in weathered exposures of tidal sandy siltstones and silty sandstones, are extremely abundant in the outcrops at the base of the Maastrichtian López de Bertodano Formation in Antarctica. Polished sections, perpendicular to bedding, show that the dimples represent voids left by eroded terminal backfilled muddy globular fecal masses inside the central tunnel of the burrow and that the globular fecal masses are totally surrounded by a terminal-radial backfill of lobate, crescentic laminae of the enveloping zone. While uniserial to multiserial pustules of the external hyporelief are known in several ichnospecies of Nereites, the alternating biserial row of fecal masses inside the central tunnel is a diagnostic ichnospecific feature, accordingly Nereites biserialis (Seilacher) is considered a valid ichnospecies.